2017
DOI: 10.18535/jmscr/v5i5.32
|View full text |Cite
|
Sign up to set email alerts
|

To Study Effectiveness of Nasal Prong and Nasal Mask in Nasal Continuous Positive Airway Pressure in Preterm Neonates with Respiratory Distress

Abstract: (112.5-354) in nasal prong group whereas nasal mask group median duration (IQR) of total hospital stay was 264 hrs .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Selection bias: we scored low for the risk of selection bias for the six trials where the methodology was adequate 5‐8,12,23 . The methodology was unclear among the remainder trials (did not specify randomization [n = 3] 11,21,22 or allocation concealment methods [n = 3] 9,10,22 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selection bias: we scored low for the risk of selection bias for the six trials where the methodology was adequate 5‐8,12,23 . The methodology was unclear among the remainder trials (did not specify randomization [n = 3] 11,21,22 or allocation concealment methods [n = 3] 9,10,22 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many clinical trials investigated the effect of NCPAP given via nasal masks compared with binasal prongs on the incidence of intubation within 72 hours. [5][6][7][8][9][10][11][12] However, only a few clinical trials showed NCPAP provided with nasal mask reduces the risk of intubation as compared with NCPAP given with binasal prongs. 8,12 Systematic reviews and meta-analyses of these clinical trials showed a similar benefit of reduced risk of intubation when NCPAP is provided with nasal masks compared with binasal prongs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent in vivo studies comparing mask and short binasal prong interfaces have suggested that masks are similarly effective to prongs, and in some respects they may present an advantage 20–25. There are now five published randomised controlled trials comparing nasal masks and binasal prongs for CPAP administration in preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…Short binasal prongs are known to cause septal trauma, which was reduced with the use of nasal masks. However, masks have been associated with nasal bridge trauma 7 20 21 24 25. This has led to the current practice in many units of cycling between masks and prongs 7.…”
Section: Discussionmentioning
confidence: 99%